Sonic Hedgehog Induces Mesenchymal Stromal Cell Senescence-Associated Secretory Phenotype and Chondrocyte Apoptosis in Human Osteoarthritic Cartilage - Feng, Meng; Liu, Wenguang; Ding, Jing; Qiu, Yusheng; Chen, Qian (Frontiers in Cell and Developmental Biology, 2021)
Hedgehog signaling plays a critical role in osteoarthritis (OA) pathogenesis, but the molecular mechanism remains to be elucidated. We show here that Sonic Hedgehog (SHH) gene expression is initiated in human normal cartilage stromal cells (NCSC) and increased in OA cartilage mesenchymal stromal cells (OA-MSC) during aging. Manifesting a reciprocal cellular distribution pattern, the SHH receptors PTCH1 and SMO and transcription factors GLI2 and GLI3 are expressed by chondrocytes (OAC) in OA cartilage. SHH autocrine treatment of osteoarthritis MSC stimulates proliferation, chondrogenesis, hypertrophy, and replicative senescence with elevated SASP gene expression including IL1B, IL6, CXCL1, CXCL8. SHH paracrine treatment of OAC suppresses COL2A1, stimulates MMP13, and induces chondrocyte apoptosis. OA-MSC conditioned medium recapitulates the stimulatory effects of SHH on OAC catabolism and apoptosis. SHH knock-down in OA-MSC not only inhibits catabolic and senescence marker expression in OA-MSC, but also abolishes the effect of OA-MSC conditioned medium on OAC catabolism and apoptosis. We propose that SHH is a key mediator between OA-MSC and OA chondrocytes interaction in human OA cartilage via two mechanisms: 1) SHH mediates MSC growth and aging by activating not only its proliferation and chondrogenesis, but also low-grade inflammation and replicative senescence, and 2) SHH mediates OA-MSC-induced OAC catabolism and apoptosis by creating a pro-inflammatory microenvironment favoring tissue degeneration during OA pathogenesis.